NDRG1 deficiency is associated with regional metastasis in oral cancer by inducing epithelial–mesenchymal transition. (29th February 2020) - de Lima, Jefferson Muniz; Morand, Grégoire B; Macedo, Carolina Carneiro Soares; Diesel, Luciana; Hier, Michael P; Mlynarek, Alex; Kowalski, Luiz P; Maschietto, Mariana; Alaoui-Jamali, Moulay A; da Silva, Sabrina Daniela
Abstract: Regional metastasis is the single most important prognostic factor in oral squamous cell carcinoma (OSCC). Abnormal expression of N-myc downstream-regulated genes ( NDRGs ) has been identified to occur in several tumor types and to predict poor prognosis. In OSCC, the clinical significance of deregulated NDRG expression has not been fully established. In this study, NDRG1 relevance was assessed at gene and protein levels in 100 OSCC patients followed up by at least 10 years. Survival outcome was analyzed using a multivariable analysis. Tumor progression and metastasis was investigated in preclinical model using oral cancer cell lines (HSC3 and SCC25) treated with epidermal growth factor (EGF) and orthotopic mouse model of metastatic murine OSCC (AT84). We identified NDRG1 expression levels to be significantly lower in patients with metastatic tumors compared with patients with local disease only ( P = 0.001). NDRG1 expression was associated with MMP-2, -9, -10 ( P = 0.022, P = 0.002, P = 0.042, respectively) and BCL2 ( P = 0.035). NDRG1 lower expression was able to predict recurrence and metastasis (log-rank test, P = 0.001). In multivariable analysis, the expression of NDRG1 was an independent prognostic factor (Cox regression, P = 0.013). In invasive OSCC cells, NDRG1 expression is diminished in response to EGF and this was associated with a potent induction of epithelial–mesenchymal transition phenotype. This result was further confirmed in an orthotopic OSCC mouse model. Together, this data support that NDRG1 downregulation is a potential predictor of metastasis and approaches aimed at NDRG1 signaling rescue can serve as potential therapeutic strategy to prevent oral cancer progression to metastasis. Abstract : NDRG1 downregulation is a predictor of metastasis in oral cancer. Interfering with NDRG1 and its upstream proteins may result in rescue of NDRG function and suppression of metastatic properties.